Aerobic Endurance Development in 13 and 14 Year-Old Swimmers - C. Tartalranu; D. Ortanescu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
In the specialized literature, physical effort is considered a request of the body above the rest level, a stimulus applied in order to adapt. Sporting physical effort determines the modification of homeostasis, stabilizing it in a certain period of time, at a higher level. In swimming, the effort capacity depends on the capacity to capture, transport and use oxygen. From an energetic and biochemical point of view, the swimmers' effort falls into the predominantly aerobic type. Directing the effort in the training session is the key to success in sports performance as well as the longevity of the individual in performance sport. The purpose of this study is to demonstrate that the methods used in training have the intended effectiveness.